Eliciators increase gas exchanges and induce the Zea mays antioxidant system - da Silva Martins, João Victor; Florêncio da Silva, Hilderlande; Oliveira Sousa, Valéria Fernandes; da Silva, Toshik Iarley; Jardelino Dias, Thiago; Souto Ribeiro, Wellington; do Nascimento, Luciana Cordeiro (Emirates Journal of Food and Agriculture, 2022)
The plant elicitors use as an agricultural input is limited and few studies show their influence on physiological responses. However, its use can induce broad-spectrum and long-lasting resistance in plants by inducing defense systems, primary and secondary metabolism. The the aim of this study was to evaluate the gas exchange (gs, A, E, Ci, WUE, iWUE and iCE) and enzymatic antioxidant system (POD, PPO and PAL) of Z. mays under elicitors application. The experiment was carried out in a completely randomized design with seven treatments: control (sterilized distilled water); Rocksil® (3 g L-1); Poagrim® (3 g L-1); Bion® (0.4 g L-1); Agrosilicon Plus® (3 g L-1); Ecolife® (3 mL L-1); Thiabendazol® (1 g L-1), with four repetitions and three plants per repetition. Gas exchange (net photosynthesis [A], stomatal conductance [gs], internal carbon concentration [Ci], transpiration rate [E], instantaneous water use efficiency [WUE= A/E], intrinsic water use efficiency [iWUE= A/gs], instantaneous carboxylation efficiency [iCE= A/Ci], and enzymatic activity (peroxidase [POX], polyphenol oxidase [PPO], phenylalanine ammonia-lyase [PAL]) were evaluated at 40 and 45 days after sowing. Gs, A, WUE, iCE and peroxidase activity increased in plants whose seeds were soaked with Rocksil® and Thiabendazol®. The phenylalanine ammonia-lyase activity was reduced in plants from seeds soaked in Ecolife®. The elicitors increased the gas exchange and antioxidant system of Zea mays L.